2022
DOI: 10.1093/ofid/ofac158
|View full text |Cite
|
Sign up to set email alerts
|

Singing Is a Risk Factor for Severe Acute Respiratory Syndrome Coronavirus 2 Infection: A Case-Control Study of Karaoke-Related Coronavirus Disease 2019 Outbreaks in 2 Cities in Hokkaido, Japan, Linked by Whole Genome Analysis

Abstract: Background Singing in an indoor space may increase the risk of SARS-CoV-2 infection. We conducted a case-control study of karaoke-related COVID-19 outbreaks to reveal the risk factors for SARS-CoV-2 infection among individuals who participate in karaoke. Methods Cases were defined as people who enjoyed karaoke at a bar and who tested positive for SARS-CoV-2 by RT-PCR between May 16 and July 3, 2020. Controls were defined as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…4 a)). The calculated high infection risk for singing is supported by several previous singing-related COVID-19 outbreaks: the karaoke-related outbreaks in bars in Sapporo and Otaru (Japan) [ 71 ], the indoor choir rehearsals in Whir au Val (France) [ 72 ], Amsterdam (The Netherlands) [ 73 ] and Skagit County ( ) [ 74 ]. As the pandemic progressed, new and more infectious variants of SARS-CoV-2 emerged.…”
Section: Resultsmentioning
confidence: 63%
“…4 a)). The calculated high infection risk for singing is supported by several previous singing-related COVID-19 outbreaks: the karaoke-related outbreaks in bars in Sapporo and Otaru (Japan) [ 71 ], the indoor choir rehearsals in Whir au Val (France) [ 72 ], Amsterdam (The Netherlands) [ 73 ] and Skagit County ( ) [ 74 ]. As the pandemic progressed, new and more infectious variants of SARS-CoV-2 emerged.…”
Section: Resultsmentioning
confidence: 63%
“…Breathing produces fewer and smaller particles than singing and speaking ( 35 ). Underpinned by the observation that engaging in karaoke (singing in the company of others, often in small rooms) involves an increased risk of spreading infections viruses ( 185 ). A study by Hersen et al ( 186 ) showed that exhaled breaths from subjects with symptoms of respiratory infections contained more small aerosols (particles <1 μm) than exhaled breaths from healthy subjects.…”
Section: Resultsmentioning
confidence: 99%
“…Karaoke and group singing are popular social activities among the elderly in Japan [ 19 ]. Increased risk of SARS-CoV-2 infection was reported when large groups of people participated in karaoke in an enclosed, poorly ventilated room [ 19 , 20 ]. In the third period, SARS-CoV-2 infection spread mainly among those in their 20s to 50s, largely within families, nursing homes, and companies.…”
Section: Discussionmentioning
confidence: 99%